(3x^2+2x-3)-(x^2-2x+1)

would the answer be 2x^2+4x+4

or did I do something wrong

2 answers

No, it would be 2x^2+4x-4
(3x^2+2x-3)-(x^2-2x+1) =

3x^2 + 2x -3 - x^2 +2x -1 =

3x^2 - x^2 + 2x + 2x -3 -1 =

2x^2 + 4x - 4
Similar Questions
  1. 9) Find q if p = -12 and the quotient p/q = -3.a) -4 (wrong) b) 4* c) -1/4 (only the one is minus) d) 1/4 19) 32 รท 24 is
    1. answers icon 2 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. I had a quiz in math.The problem is: |4.3+(-7.2)| I got the answer 11.5 and my teachr marked it wrong. When she gave us a chance
    1. answers icon 6 answers
more similar questions